Menu Costs and Inflation Asymmetries Some Micro Data Evidence - Péter Karádi; Àdám Reiff (Hungarian Academy of Sciences, Institute of Economics, 2007)
The paper explains the observed asymmetric inflation response to value-added tax (VAT) changes in Hungary by calibrating a standard sectoral menu cost model on a new micro-level CPI data set. The model is able to reproduce important moments of the data, and finds that the asymmetry can be explained by the interaction of menu costs, (sectoral) trend inflation and forward-looking firms, thereby it provides direct evidence to the argument of Ball and Mankiw (1994).
Keywords: E30; 330; Menu Cost; Inflation Asymmetry; Sectoral Heterogeneity; Value-Added Tax; Anpassungskosten; Schock; Inflation; Preismanagement; Preisrigidität; Umsatzsteuer; Theorie; Schätzung; Ungarn